A ferry runs between two landing piers and on diagonally opposite sides of the river. While the ferry moves with a velocity of relative to the water, the river itself has a flow velocity of In order not to be driven off, the boat must steer towards the opposite direction of the flow.
In the best case, how long does it take for the boat to make a round trip between and
Note:
The hold at the pier and the turning maneuver are neglected.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The velocities v i and u of the boat and the flow add up to the total velocity w i , that is aligned parallel to the line A B (with index i = 1 , 2 ). This can be graphically represented by the correspondings vector parallelograms:
With the help of angles α 1 and α 2 we can represent the vector addition by the follows sets of equations: w 1 = ( w 1 / 2 w 1 / 2 ) w 2 = ( − w 2 / 2 − w 2 / 2 ) = ( v cos α 1 v sin α 1 ) + ( 0 u ) = v 1 + u ( 1 ) = ( − v cos α 2 − v sin α 2 ) + ( 0 u ) = v 2 + u ( 2 ) By elimination of the variable w i , we obtain the following equations: v cos α 1 v cos α 2 = v sin α 1 + u = v sin α 2 − u ⇒ cos α 1 − sin α 1 ⇒ cos α 2 − sin α 2 = v u = − v u With the help of the Pythagorean theorem sin 2 x + cos 2 y = 1 and the addition theorem sin ( x + y ) = sin x cos y + cos x sin y we can simplify the left hand side of both formulas: ( cos α − sin α ) 2 ⇒ α = cos 2 α − 2 cos α sin α + sin 2 α = 1 − sin 2 α = ( v u ) 2 = 2 1 arcsin ( 1 − ( v u ) 2 ) = 2 1 arcsin 2 5 1 6 = 1 9 . 9 ∘ or 7 0 . 1 ∘ The different solutions corresponds to the different angles α 1 and α 2 . Substituting these numbers into the equations (1) and (2) yields the total velocities. w 1 w 2 = 2 v cos α 1 = 6 . 6 5 s m = 2 v cos α 2 = 2 . 4 1 s m Therefore, the total traveling time T results T = t 1 + t 2 = w 1 s + w 2 s = 6 . 6 5 m / s 2 ⋅ 2 0 0 m + 2 . 4 1 m / s 2 ⋅ 2 0 0 m ≈ 1 6 0 s